DISTRIBUCIÓN DE PROBABILIDAD QUE INVOLUCRA ALGUNAS FUNCIONES HIPERGEOMÉTRICAS GENERALIZADAS - Meléndez, Rafael Alfonso; Castillo, Jaime Antonio; Jiménez, Carlos Jesús (Revista Colombiana de Estadística, 2010)
We define a new function of probability that involves some generalized hypergeometric functions, we found some properties and special cases such as gamma and exponential. We establish some basic functions associated with the new probability distribution like mean, the moments, characteristic function and several graphic representations are obtained for this new function of probability.